Education on Income Tax (PPh) Badan: Edukasi pajak Penghasilan (PPh) Badan - Hardi; Nofrizal; Lubis*, Nurhayani; Siregar, Inova Fitri; Maryanti, Sri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The background of partner selection is based on the situation analysis that students at the school are still not fluent in calculating corporate income tax 21. So that it requires additional understanding of this matter. To overcome the lack of ability of these students, the service team from the Faculty of Economics and Business, Lancang Kuning University offered a solution to provide education about PPh 21 corporate tax. And it was welcomed by the school. The purpose of this service is to improve the ability of students majoring in accounting at SMKN 1 Tapung in calculating income tax This service was carried out on 15 August 2023 at SMKN 1 Tapung. This service was carried out on 15 August 2023 at SMKN 1 Tapung. To achieve the service objectives that have been previously stated, the implementation of this community service activity is carried out with a systematic method, which begins with the preparation stage, namely discussing with the school regarding what the current needs of students are and formulating the solutions provided. After that, enter the second stage, namely the implementation stage, at this stage the team provides education about corporate income tax 21 to students. This stage was attended by 29 students majoring in accounting. At this stage, students are directly involved in tax calculations so that students understand more about the concepts and how the calculation of PPh 21 Corporate tax applies in Indonesia. The last stage is evaluation, where this stage is one of the most important. Evaluation is intended to measure the success of this service. Evaluation is measured by giving questionnaires before and after the service. The results of the questionnaire from 29 students showed a significant improvement, and it can be concluded that this service was successful. As a continuation, it is hoped that the school can continue to educate students about the tax regulation updates. Because as is known, the regulations regarding taxes are constantly evolving